2014
DOI: 10.1080/03069885.2014.886670
|View full text |Cite
|
Sign up to set email alerts
|

Career construction with a gay client: a case study

Abstract: This article reports on the value of career construction counselling (CCC) with a gay person. The participant was selected purposively, with the selection criteria calling for a mid-career woman who had sought career counselling. The intervention involved administration of the Career Construction Interview (CCI) and the creation of a life portrait. A case study design (working with a participant in a one-on-one research setting and incorporating a qualitative, interpretive paradigm) was implemented. The CCI (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 6 publications
2
23
0
15
Order By: Relevance
“…These findings are consistent with those of earlier studies. Whereas Del Corso, Rehfuss, and Galvin () demonstrated the value of the CCI in enhancing the career adaptability of clients, Maree () highlighted the value of the CCI in working with members of marginalized and minority groups. Taber and Briddick () provided evidence of the value of the CCI in meeting the resilience adaptability needs of workers in the current world of work, and Taber, Hartung, Briddick, Briddick, and Rehfuss () showcased the value of the CCI in creating life portraits to inspire hope in a brighter future.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with those of earlier studies. Whereas Del Corso, Rehfuss, and Galvin () demonstrated the value of the CCI in enhancing the career adaptability of clients, Maree () highlighted the value of the CCI in working with members of marginalized and minority groups. Taber and Briddick () provided evidence of the value of the CCI in meeting the resilience adaptability needs of workers in the current world of work, and Taber, Hartung, Briddick, Briddick, and Rehfuss () showcased the value of the CCI in creating life portraits to inspire hope in a brighter future.…”
Section: Methodsmentioning
confidence: 99%
“…Authors have attempted to create new terms to describe what is currently happening in the world of work. Terms such as the following have become well known in the work-related literature (Maree, 2013(Maree, , 2014):…”
mentioning
confidence: 99%
“…Likewise, Del Corso, Rehfuss, andGlavin (2011), andTaber and demonstrated the value of the CCI in enhancing the career adaptability of clients. Maree (2014) showed the value of the CCI in working with members of marginalized and minority groups. Similarly, the findings in the present study support the findings of Hughes, Gibbons, and Mynatt (2013), who confirmed the pivotal role of career adaptability in students' career success.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interests change over time, and "[r]emaining ever open-minded is the smartest way to adapt to change" (p. 351). This helps explain the move toward an integrated, qualitative + qualitative approach and the use of qualitative and quantitative, and objective and sub-jective methods of career counseling assessment, data gathering, and counseling to elicit career-related information (Maree, 2014). Emphasis is placed on encouraging and enabling clients to express their deepest emotions and passions more openly and thereby help them identify deep-seated strengths and motives.…”
Section: Introductionmentioning
confidence: 99%